1-Dopyl-1, 2-(4-hydroxyphenyl)ethene: A flame retardant hardner for epoxy resin. (May 2020) - Howell, Bob A.; Lienhart, Gavan W.; Livingstone, Veronica J.; Aulakh, Darpandeep
Abstract: Treatment of desoxyanisoin with 9, 10-dihydro-9-oxaphosphaphenathrene-10-oxide (DOPO) in the presence of an acid catalyst generates an adduct, 1-dopyl-1, 2-(4-methoxyphenyl)ethene which may be readily converted to the corresponding diphenolic compound, 1-dopyl-1, 2-(4-hydroxyphenyl)ethene (BDE). This material behaves as an effective curing agent for the diglycidyl ether of bisphenol A (DGEBA) to provide a thermally stable (Tdec 417 °C) resin with Tg of 146 °C. This polymer displays outstanding flammability characteristics – an LOI of 36 (compared to 19 for conventionally cured resin), a total heat release of 20 kJ/g and a UL 94 V0 rating. The flame retardant impact of the incorporation of this hardner into the resin is due both to its structure (promotes char formation for solid phase activity) and the presence of the DOPO substituent (promotes gas-phase activity). Highlights: 1-Dopyl-1, 2-(4-hydroxyphenyl)ethene has been prepared and demonstrated to be an effective hardner for DGEBA epoxy. The incorporation of this hardner into epoxy imparts excellent flame retardancy. The structure of the hardner promotes char formation while the presence of the dopyl unit contributes gas-phase activity.